Quality Improvement of a Small Water Supply. A Practical Application of a Full System of Nanofiltration - Marin Galvin, R.; Rodriguez Mellado, J. M. (Engineering, Technology & Applied Science Research, 2013)
The THM level in the Spanish drinking water is limited to less than 0.100 mg/L, due to its potential toxicological effect on humans. This paper investigates the comparison of the results obtained in a small supply of water that historically presented THM contents out of the Spanish normative, versus the results there obtained when the treatment was modified with the inclusion of a nanofiltration system. So, the conventional treatment first applied was that of pre-oxidation with chlorine and/or KMnO4, followed by coagulation with aluminum salts directly on closed sand filter, and disinfection final by chlorination: with this system, THM levels lower than 0.100 mg/L were not always secured. Thus, to improve the water quality, a full system of nanofiltration was implemented, after the above treatment, consisting in: pre-filtration through cartridges, filtration over activated carbon, post-filtration for retaining impurities, and finally, nanofiltration and chlorination of water after nanofiltration. In this order, the new treatment scheme has usually produced water with maximum THM levels of 0.058 mg/L, and average values of 0.013 mg/L, 0.30 mg/L for organic matter concentrations, and water always microbiologically pure. Also, the contents of Fe, Mn and Al in the treated water were significantly reduced with respect to the previous situation without nanofiltration.